(untitled) (International Journal of Mathematics and Physics, 2022)
Based on the approach of Sagdeev pseudo-potential, the fully nonlinear structures of a four-component quantum plasma have been extensively investigated. The plasma under consideration consists of negative and positive dust particulates and quantum distributed electrons and ions. For typical plasma parameters, the bifurcation analysis enables us to distinguish three types of nonlinear waves, namely compressive soliton, rarefactive soliton and double-layer depending on the magnitude of the configurational plasma parameters. The formations and the existence ranges of both solitons and double-layers are found to be highly sensitive to the values of the chosen plasma parameters and the quantum indices as well. The implications of the obtained results have a wide relevance in the study of space and laboratory quantum dusty plasmas where the positive and negative dust particulates are presented and quantum effects are taken into account.